Tenderness of Space and Outlandish Woman The Tenderness of the Wolves and The Outlander - Polić-Jurković, Vanja (Array, 2011)
In two novels belonging to the genre of the detective fiction (Todorov) – Stef Penney’s The Tenderness of Wolves (2006) and Gil Adamson’s The Outlander (2007) – the backdrop is analyzed to reveal how the stereotypical perceptions of late 19th and early 20th century Canadian space are reworked to accommodate the development of female protagonists within generic fiction which does not usually allocate much space to character development. The stereotypical images of Canada are thus used to reveal both the space and women as sites of inscription by a white European man. The traditionally accepted binary oppositions of civilization vs. nature, savage/Native man vs. civilized/white man, man vs. woman, centre vs. periphery, are problematized and deconstructed, foregrounding the marginal characters of the settler society.